Causes of bruising in carcasses of beef cattle during farm, transport, and slaughterhouse handling in Brazil. (18th December 2018) - Mendonça, Fábio S.; Vaz, Ricardo Z.; Vaz, Fabiano N.; Leal, Willian S.; Silveira, Isabella D. B.; Restle, João; Boligon, Arione A.; Cardoso, Fernando F.
Abstract: This study aimed to assess preslaughter factors responsible for the occurrence of bruises to front, rib, loin, hip, and round sites of cattle carcasses. Data from the slaughter of 148 loads of cattle were assessed, totaling 4, 611 carcasses. Evaluated bruising factor variables were animal gender, journey distance (km), vehicle type (m²), journey time (hours), load density (kg/m 2 ), handling and facilities conditions (optimal, acceptable, and unacceptable), and unloading waiting time (min). Gender had the strongest influence on carcass bruising, being the first variable to enter in the majority of models related to the carcass sites. Female carcasses displayed higher bruising in all sites. Densities above 401 kg/m² caused more bruising. With the exception of the loin, unacceptable, and acceptable conditions assigned to farm facilities and handling resulted in higher average bruising. Articulated vehicles with a greater load capacity were more likely to cause bruising. The effects of variables causing bruises act differently in the various carcass sites. In this sense, the results of this study suggested possible management practices for specific problems during the preslaughter period to minimize losses by bruising to different carcass sites.